Studies in the staple food economy of western Nigeria : With 32 maps - Gusten, Rolf.; Nigerian Institute of Social and Economic Research (München : Weltforum Verlag, 1968)
This is a study of the staple food economy of Western Nigeria by Rolf Gusten for the Nigerian Institute of Social and Economic Research, Ibadan.
Bibliography: p. 302-304.
lje 25/1/19
Loans
Keywords: Food supply; Produce trade